Effects of short‐term nitrogen addition on the recovery of alpine grassland in the Tianshan Mountains of Xinjiang, China - Juan Wang; Junjie Liu; Chao Liu; Xiaoyu Ding; Yonggang Ma; Jianjun Yang; Zhonglin Xu (Ecology and Evolution)
Abstract The restoration of alpine grasslands has garnered significant attention across various sectors. Historically, natural restoration has been the primary approach for grassland recovery, characterized by its prolonged duration. To expedite the recovery of degraded grasslands, it is essential to identify the limiting factors of restoration, enabling efficient and rapid recovery. Appropriate nitrogen (N) addition levels have been considered a potential strategy to enhance the recovery of grassland ecosystems and augment their ecological benefits. However, the effectiveness of N addition in alpine grassland restoration remains debated. This study investigated the impact of five N addition levels (CK: control [0 g/m2]; LN: low N [5 g/m2]; MN: medium N [10 g/m2]; HN: high N [15 g/m2]; SN: severe N [20 g/m2]) and two experimental approaches (N addition once per year [NPY] and three times per year [NTY] at the same dosages) on plant and soil properties and the maximum restoration capacity of alpine meadows. Our findings reveal three key insights: The level of N addition was the primary factor influencing aboveground plant biomass and coverage. Plant diversity decreased under the NTY regime and increased with NPY in the Bayinbruck grassland. N addition significantly altered soil properties, including pH, salinity, soil organic carbon (SOC), soil‐available phosphorus (AP), and soil total phosphorus (TP). Notably, soil TP, total nitrogen (TN), and AP substantially impacted plant community structure and diversity. Based on structural equation model (SEM) and analysis of variance (ANOVA), optimal grassland restoration was achieved with the HN (15 g/m2) treatment under NPY and the MN and HN (10 and 15 g/m2) treatments under NTY. Overall, our study offers crucial insights into the conservation, management, and restoration of grassland ecosystems on the Bayinbruck Plateau. It underscores the significance of N addition effects on plant communities, vegetation restoration, and soil properties.